Abstract TMP25: The Visual Field Rapid Analysis Device (vrad) Is Safe, Effective And Easy To Use - Solenski, Nina; Allende, J. A; Aldridge, Chad; Dirghangi, Arjun; Perch, Miah; Weko, Andrew; Koyada, Prajeeth; Shabo, Leah; Gottschalk, Carter; Gunter, Sonya (Stroke (1970), 2022)
BackgroundAcute telestroke consults rely on a rapid, accurate NIH Stroke Scale. An important sign in cortical-based ischemic strokes is a Visual Field Deficit (VFD) contributing up to 3 points on the NIHSS affecting treatment decisions. Remote confrontational VFD testing is challenging and requires a trained assistant. We created a simple, rapid, telecart peripheral device to remotely administer a standardized VF test. The “V isual fields R apid A ssessment D evice” (VRAD) is a wearable eye-glasses device. The device flashes LED lights in the 4 quadrants of each eye via remote control by a teleprovider allowing real-time control and interpretation. MethodsThe VRAD Phase I study examined FDA-related human design factors of comfort, speed, and ease of use with direct use of VRAD. The results guided optimization of the prototype in preparation for the Phase II validation clinical trial. Subjects were randomly-selected, consented adult UVA Stroke Unit inpatients, with confirmed ischemic strokes. Following each VF test, blinded teleproviders, the patient ,and the telepresenter (nurse) completed a brief binary response questionnaire with open-ended comments. Biostatistical analysisN= 20 subjects; 95% confidence interval with precision of +/- 10%. ResultsThe vast majority of patients, presenters, and providers (95-100%) reported VRAD testing was easy to understand and rapid. PatientsThe device was comfortable (90%); 10% felt the stimulus light was too bright and 5% too dim. All identified when the light was on and had enough time to respond. PresentersAll reported rapid testing; 75% felt the device was easy to don on patients. The device was “sturdy and durable” 90%, “easy to use” 75%, “easy to clean” 70%, and “easy to connect” 60%. ProvidersReported the device sufficiently screened standard VFs (90%). All agreed they could remotely administer the test in various settings. ConclusionThe VRAD Phase I trial found the device to be safe, effective, easy to use, and comfortable by patients, providers, and presenters. Based on the results, an upgraded prototype was manufactured for our upcoming Phase II Non-Inferiority Validation Trial (Fall 2021). This data is a proof-of-concept of the value of teleneurology peripheral tools in remote settings.